2014
DOI: 10.2147/ijn.s60274
|View full text |Cite
|
Sign up to set email alerts
|

Preparation and properties of poly(vinyl alcohol)/chitosan blend bionanocomposites reinforced with cellulose nanocrystals/ZnO-Ag multifunctional nanosized filler

Abstract: A series of novel bionanocomposites were cast using different contents of zinc oxide-silver nanoparticles (ZnO-AgNPs) stabilized by cellulose nanocrystals (CNC) as multifunctional nanosized fillers in poly(vinyl alcohol)/chitosan (PVA/Cs) matrices. The morphological structure, mechanical properties, ultraviolet-visible absorption, and antimicrobial properties of the prepared films were investigated as a function of their CNC/ZnO-AgNP content and compared with PVA/chitosan/CNC bionanocomposite films. X-ray diff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
14
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 83 publications
(15 citation statements)
references
References 41 publications
1
14
0
Order By: Relevance
“…These findings suggest that the inclusion of nanoparticles did not change the structure of the matrix. According to Azizi et al [44], the fact of there was neither new peaks nor peak shifts compared with Ch pattern would be consistent with the coexistence of two phases (polymer and nanoparticles). The average crystallite size was calculated from XRD peak located at 18°based on the Debye-Scherrer equation [45,46]:…”
Section: X-ray Studiesmentioning
confidence: 79%
“…These findings suggest that the inclusion of nanoparticles did not change the structure of the matrix. According to Azizi et al [44], the fact of there was neither new peaks nor peak shifts compared with Ch pattern would be consistent with the coexistence of two phases (polymer and nanoparticles). The average crystallite size was calculated from XRD peak located at 18°based on the Debye-Scherrer equation [45,46]:…”
Section: X-ray Studiesmentioning
confidence: 79%
“…Adsorbent for the removal of heavy metal ions [160][161][162] Adsorbent for the removal of acidic reagents, metals, amino acids, proteins, and other compounds [163] Biocomposite films [164,165] Biomedical applications [166] Coronary artery bypass graft [167] Drug delivery [168] Electronic [169] Food packaging [170] Medical material [171] Odor treatment [172] Self-healing [173] Textiles [174] Wound dressing [175,176] Wound healing (good antibacterial effect) [177] 9.1. Drug Delivery Nowadays, controlled drug delivery provides many advantages to humans, e.g., it can enhance efficacy and reduce or eliminate unwanted side effects and also the level of drugs.…”
Section: Potential Applications Referencesmentioning
confidence: 99%
“…Ravichandran [38] has also reported that the mechanical properties of PVA film can be strengthened when doped with nano zinc oxide particles. Azizi et al [39] have observed that in comparison to the poly(vinyl alcohol)/chitosan, filled polymer blend showed an increase trend in tensile properties, but the reinforcing effect of cellulose (CNC) was less than that of the CNC/ZnO-Ag NPs.…”
Section: Mechanical Propertiesmentioning
confidence: 99%